2021
DOI: 10.38212/2224-6614.3349
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of L-theanine in tea extracts and synthetic products using Stable Isotope Ratio Analysis

Abstract: L-theanine involves a great number of health benefits and dietary supplements containing this molecule are becoming increasingly popular. There is, therefore, a growing need to find ways to discriminate between natural L-theanine extracted from tea leaves and the cheaper, synthetic one obtained using specific bacterial enzymes. A first attempt of stable isotope ratio analysis characterization of the possible synthetic adulterant L-theanine (δ 13 C of −14.3 ± 1.5‰), obtained from vegetabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The δ 13 C protein values in the rice vinegar samples were from −25.99‰ to −28.26‰ ( Table 1 ) and fell within the typical δ 13 C range of −23‰ to −30‰ for C3 plants [ 24 ] due to the C3 plant derived raw materials of these samples, such as rice, waxy rice, wheat, or malt. Our previous study [ 17 ] showed that the δ 13 C acetic acid values in the A1 to A4 samples using the C4 plant derived ethanol as the main raw material shifted to the typical δ 13 C range of −9‰ to −15‰ for C4 plants [ 25 ].…”
Section: Resultsmentioning
confidence: 83%
“…The δ 13 C protein values in the rice vinegar samples were from −25.99‰ to −28.26‰ ( Table 1 ) and fell within the typical δ 13 C range of −23‰ to −30‰ for C3 plants [ 24 ] due to the C3 plant derived raw materials of these samples, such as rice, waxy rice, wheat, or malt. Our previous study [ 17 ] showed that the δ 13 C acetic acid values in the A1 to A4 samples using the C4 plant derived ethanol as the main raw material shifted to the typical δ 13 C range of −9‰ to −15‰ for C4 plants [ 25 ].…”
Section: Resultsmentioning
confidence: 83%
“…The Global Network of Isotopes in Precipitation (GNIP) database, administered by the International Atomic Energy Association (IAEA) and the World Meteorological Organization (WMO), is recognized as a useful method to evaluate the correlation between the δ 2 H of rainwater and groundwater in the absence of direct measurement [39]. The GNIP database (http://www-naweb.iaea.org/ napc/ih/documents/userupdate/Waterloo/, accessed on 1 January 2023) contains monthly weighted average precipitation (δ 2 Hp and δ 18 Op) from all continents and islands between 1960 and the present. The temperature and the amount of precipitation significantly influence the δ 2 H values of the water.…”
Section: δ 2 H Of Natural and Synthetic Curcuminoid Complexmentioning
confidence: 99%
“…In recent years, stable isotope ratio analysis (SIRA) found widespread use in food science [16], not only to trace the geographical origin of products, but also to guarantee their authenticity, differentiating between natural and synthetic or biosynthetic ingredients [17][18][19][20][21]. In the latter case, applications of the SIRA involved nutraceutical products or products with pharmacological properties that are increasingly in demand due to their natural origin [18,21,22]. The SIRA is based on the measurement of the ratio between the heavy and light isotopes of the elements carbon ( 13 C/ 12 C), nitrogen ( 15 N/ 14 N), sulfur ( 34 S/ 32 S), oxygen ( 18 O/ 16 O) and hydrogen ( 2 H/ 1 H).…”
Section: Introductionmentioning
confidence: 99%
“…The stable isotope analysis of bio-elements has already been successfully tested as a technique for distinguishing different natural molecules from their synthetic and/or biosynthetic counterparts. These molecules include, e.g., monacolin K from fermented red rice [22], theanine [23], curcuminoids [24], and vanillin [25]. The 13 C/ 12 C isotope ratios of carbon (expressed as δ 13 C), the 18 O/ 16 O ratios of oxygen (δ 18 O), and the 2 H/ 1 H ratios of deuterium (δ 2 H) proved to be effective in the discrimination between the active principal compound of interest obtained from natural sources and that obtained from fossil sources used in the industrial synthesis.…”
Section: Introductionmentioning
confidence: 99%